2014
DOI: 10.3109/13697137.2014.933409
|View full text |Cite
|
Sign up to set email alerts
|

Menopause is associated with lumbar disc degeneration: a review of 4230 intervertebral discs

Abstract: Objective The main objective of this study was to investigate, in a population of normal postmenopausal women, the association between menopause and severity of lumbar disc degeneration from the fi rst lumbar to the fi rst sacral vertebra on magnetic resonance imaging.Methods Between January 2010 and May 2013, 846 normal women and 4230 intervertebral discs were retrospectively analyzed. Age, height, weight and years since menopause (YSM) were recorded. Disc degeneration was evaluated using the modifi ed Pfi rr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Estrogens can maintain collagens that protect the intervertebral disk [ 42 ]. Lou et al found a relationship between menopause and the degeneration of intervertebral disk [ 43 ]. Moreover, the changes in hormone levels during menopause could lead to the degeneration of vertebral endplate, which affected the nutritional distribution of the intervertebral disk, ending in the degeneration of the spine [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens can maintain collagens that protect the intervertebral disk [ 42 ]. Lou et al found a relationship between menopause and the degeneration of intervertebral disk [ 43 ]. Moreover, the changes in hormone levels during menopause could lead to the degeneration of vertebral endplate, which affected the nutritional distribution of the intervertebral disk, ending in the degeneration of the spine [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significantly lower intervertebral disc height was demonstrated in postmenopausal osteoporotic women when compared with that in untreated nonosteoporotic women who, in turn, had significantly lower disc height than premenopausal women and women taking MHT [77]. Intervertebral disc space shows a progressive decline that almost entirely occurs in the first 5-10 years after menopause [78]. Estrogen was shown to have direct chondroprotective effects and to be able counteract cartilage degradation in an in vivo model of increased cartilage turnover [79].…”
Section: Bone Effects Of Menopausal Hormone Therapymentioning
confidence: 99%
“…Recent studies have provided increasing evidence that osteoporosis is associated with the evolution of IVDD. The osteoporosis of vertebrae in postmenopausal women was correlated with IVDD [ 20 , 21 ], and sex hormones can affect the severity of IVDD [ 21 23 ]. Furthermore, in osteoprotegerin (OPG) knockout mice, ossification occurred in the cartilage endplate and resulted in IVDD [ 24 ].…”
Section: Introductionmentioning
confidence: 99%